Análisis técnico comparativo de herramientas de escaneo de puertos de redes de telecomunicaciones - Valencia Martínez, Geovanny Giussepe (2023)
Comparing tools such as Nmap, Netcat and Unicornscan to see which ones are the fastest and easiest to use for scanning telecommunication networks is useful, but remember, using these tools in an ethical way is very important, because ethical hacking is a legal practice that helps to find problems in computer systems, such as WiFi networks. When you do ethical hacking, you need permission from the network owner to avoid legal problems, because all these tools help us to simulate real attacks and find various security problems, because Nmap, Netcat and Unicornscan are useful because they do this in different ways. It is vital to keep your security measures up to date and secure, as computer threats change, so you need to be aware of the latest security practices and apply them in a world where attack methods are evolving rapidly and hackers are getting smarter and smarter.